2001
DOI: 10.4321/s0212-71992001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Anemia e incapacidad funcional al ingreso en una residencia geriátrica

Abstract: Aunque la anemia es frecuente en el anciano, no debe ser atribuida sin más a la edad avanzada (1). Aun en la persona mayor, la presencia de anemia indica alto riesgo de enfermedad subyacente (2). En el anciano las anemias suelen ser multifactoriales, pero se han encontrado asociadas hasta en un 44 % de los casos a un déficit de nutrientes necesarios para la hemopoyesis, tales como el hierro, la vitamina B12, y los folatos (3). Dada la frecuencia de la patología tiroidea en las personas mayores (4), así como la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The prevalence of thyroid dysfunction found in the present study was similar to that reported in other studies performed in aged population in our country, which ranged from 4 to 13%. [14][15][16][17][18][19][20] Although it has been generally admitted that the prevalence of thyroid dysfunction in the elderly is higher in hospitalized and institutionalized patients than in general population, 21-24 these findings have not been confirmed in elderly population in our area. 18 It is remarkable that prevalence of thyroid dysfunction found in Spanish populations has been lower than that reported in American population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thyroid dysfunction found in the present study was similar to that reported in other studies performed in aged population in our country, which ranged from 4 to 13%. [14][15][16][17][18][19][20] Although it has been generally admitted that the prevalence of thyroid dysfunction in the elderly is higher in hospitalized and institutionalized patients than in general population, 21-24 these findings have not been confirmed in elderly population in our area. 18 It is remarkable that prevalence of thyroid dysfunction found in Spanish populations has been lower than that reported in American population.…”
Section: Discussionmentioning
confidence: 99%